"I Couldn't Do It to a Kid Knowing What It Did to Me": The Narratives of Male Sexual Abuse Victims' Resiliency to Sexually Offending. (June 2016) - Lambie, Ian; Johnston, Emma
Research has shown that child sexual abuse victims are overrepresented among sexual abuse offenders, leading to the sexually abused–sexual abuser hypothesis. However, a large proportion of child sexual abuse victims do not go on to sexually offend, and such individuals are labeled as resilient victims. Surprisingly few studies have looked at why some male victims of sexual abuse do not go on to offend. In-depth qualitative interviews were conducted with 47 resilient men focusing on their beliefs as to why they had not gone on to sexually abuse others. Results revealed four themes for why the victims did not offend: empathy, morals, lack of sexual desire, or a combination of the previous three. In regard to the process of developing their resiliency, some participants claimed they made a conscious decision, whereas others reported the decision was an unconscious one. The various factors that were reported as contributing to the conscious or unconscious decision (becoming aware of sexual abuse, admitting the experience had happened to them, empathy, social support, and lack of sexual desire to abuse) are discussed, along with the four themes, and the implication of these results for prevention. Finally, conclusions are drawn that the victim–offender pathway is far from inevitable as most participants stated their reason for not offending was directly related to their own experience of sexual abuse victimisation.